(untitled) (Annual of the Faculty of Philosophy in Skopje, 2010)
The emergence of feminist ethics, as a new field in the framework of traditional western ethics, is a product of the efforts of those who support women’s rights and their liberation from all forms of domination and discrimination. They have renounced their voice through the women’s movement, known a feminist movement. In the “gillan offensive” for true equality between men and women in society, the activism of modern feminism from the 1960 ’s isn’t only directed at resolving and improving the women’s social status, but also at correcting the way to conceive the woman’s world, which predominates in social sciences. This work focuses on feminist ethics, in an attempt to audit, reformulate, i.e. to reconsider those aspects of the traditional western ethics, which underrate the moral experience of women. Utilizing a wide range of various ethical approaches and choices, this work shows the efforts of the feminists to cross the boundaries of morality created exclusively on male moral values, as well as their recognition and the equal status of women as a moral entity. Because the common goal of all feminist approaches towards ethics is to create equal gender ethics, a moral theory based on non-sexist moral principles, policies and practices, this work emphasizes the importance of feminist ethics, based on different ontological and epistemological assumptions, which instead of separating people with a superior, elitist attitude towards "the others", will join them in their mutual relations.